2018
DOI: 10.1080/13676261.2018.1523539
|View full text |Cite
|
Sign up to set email alerts
|

Everyday negotiations of belonging - making Mexican masks together with unaccompanied minors in Finland

Abstract: In this paper we discuss how art workshops can be used to examine dimensions of belonging. We draw on our findings of collaborative ethnographic fieldwork with unaccompanied refugee minors in Finland. The practical aim of the art project was to offer a platform for transcultural communication and interaction, and to support mutual understanding and solidarity among the refugee minors and Finnish pupils. The collaborative ethnographic approach gave us an opportunity to meet the young people through working toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
4
0
2
Order By: Relevance
“…This is in line with prior studies that have shown that connectedness, a decent socioeconomic situation, stable living conditions, and opportunities to learn the language, support integration (Carswell et al, 2011;Varvin, 2017;Vervliet et al, 2014). Moreover, prior studies indicate that creatives activities might be a context in which youth from different backgrounds can encounter each other, and understand social codes (Korjonen-Kuusipuro, Kuusisto, & Tuominen, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with prior studies that have shown that connectedness, a decent socioeconomic situation, stable living conditions, and opportunities to learn the language, support integration (Carswell et al, 2011;Varvin, 2017;Vervliet et al, 2014). Moreover, prior studies indicate that creatives activities might be a context in which youth from different backgrounds can encounter each other, and understand social codes (Korjonen-Kuusipuro, Kuusisto, & Tuominen, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Ahmed (1999) asserts that the issues of migration automatically relate to the concept of home, which in turn is linked to issues of belonging (e.g. Korjonen-Kuusipuro, Kuusisto, & Tuominen, 2018). A similar perspective is brought up by Wernesjö (2015), highlighting the necessity of understanding home and belonging as processes that may change over time.…”
Section: Belongingmentioning
confidence: 99%
“…For young people with backgrounds of migration a sense of safety within relationships has often been broken. This happens through diverse and complex experiences but has lasting effects on young people's abilities to feel safe, stable and to trust (Korjonen-Kuusipuro et al 2018). Issues and questions around trust, in particular around fear of judgment from others, existed within the group.…”
Section: Building Relationships and Trustmentioning
confidence: 99%
“…The further development of this work with young migrants, together with young people marginalized within the care system more broadly, may create opportunities for young people to come together and learn across perceived lines of difference, building towards more inclusive societies. Additionally, by developing this work with other young people within the communities where these young people currently live, and will be transitioning into, it may become possible for young people to translate their knowledge into concrete action, and make meaningful connections with their future selves, and future lives (Korjonen-Kuusipuro et al 2018).…”
Section: Implications For Building Belonging With Young Migrants In Carementioning
confidence: 99%